Engineering Fe and V Coordinated Bimetallic Oxide Nanocatalyst Enables Enhanced Polysulfides Mediation for High Energy Density Li‐S Battery. Issue 28 (19th June 2022) - Cheng, Hao; Zhang, Shichao; Li, Siyuan; Gao, Cheng; Zhao, Sihan; Lu, Yingying; Wang, Miao
Abstract: Lithium sulfur (Li‐S) batteries are expected to become the next‐generation rechargeable energy storage devices owing to their high theoretical energy density, environmental benignity, and economic benefits. However, the undesirable lithium polysulfides (LiPSs) shuttling and sluggish redox kinetics of sulfur electrochemistry severely degenerate the wide‐ranging electrochemical performances, hindering the commercialization process of Li‐S batteries. Herein, a Fe and V coordinated bimetallic oxide FeVO4 (denote FVO) nanocatalyst with three‐dimensional (3D) ordered structure is thoughtfully tailored and cooperated with the commercialized carbon nanotubes (CNT) to modify polypropylene (PP) separator for achieving high efficiencies of restraining the LiPSs shuttling and boosting the redox conversion of sulfur species. The Fe and V coordinated bimetallic oxide demonstrates enhanced anchoring and catalyzing activities toward sulfur species than single metal oxides of Fe and V with homometallic valence states due to the reconfiguration of the 3d‐band. Impressively, the Li‐S pouch cell with the FVO/CNT@PP separator achieves an energy density up to 341 Wh kg −1 . The bimetallic oxide nanocatalyst used in this work enlightens a new designing route toward the separator modification for the development of high energy density Li‐S batteries. Abstract : This study reports that a Fe and V coordinated bimetallic oxide FeVO4 (FVO) nanocatalyst with three‐dimensional ordered structure synthetized by a template method cooperates with carbon nanotubes (CNT) to modify polypropylene (PP) separator for achieving a high‐energy‐density lithium sulfur battery.